1993
DOI: 10.1111/j.1740-8261.1993.tb02018.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Urinary Tract Obstruction in Dogs Using Duplex Doppler Ultrasonography

Abstract: The ability of duplex Doppler ultrasonography to assist with the diagnosis of urinary tract obstruction was investigated in a study of 5 dogs with surgically induced, unilateral ureteral obstruction. The resistive index (RI) of obstructed kidneys was compared to that of controls and to the contralateral unobstructed kidneys. The RI was also evaluated following relief of obstruction. On the basis of an RL measurement 20.70 indicating obstruction, a sensitivity of 73% and a specificity of 77% was determined for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
15

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 9 publications
4
56
1
15
Order By: Relevance
“…The resistive index obtained during Doppler sonography has been used to estimate alterations in vascular resistance provoked by renal disease, unilateral ureteral obstruction induced by surgery, and diuretic actions among others (Nyland et al 1993;Rivers et al 1997;Choi et al 2003). Mean renal resistive indices of 0.64 § 0.03 (Choi et al 2003), and 0.72 (Novellas et al 2007) have been reported in dogs with normal kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…The resistive index obtained during Doppler sonography has been used to estimate alterations in vascular resistance provoked by renal disease, unilateral ureteral obstruction induced by surgery, and diuretic actions among others (Nyland et al 1993;Rivers et al 1997;Choi et al 2003). Mean renal resistive indices of 0.64 § 0.03 (Choi et al 2003), and 0.72 (Novellas et al 2007) have been reported in dogs with normal kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…As artérias interlobulares originam-se das artérias arqueadas e tornam-se visíveis usando-se Doppler colorido. As veias geralmente são mais largas do que as artérias adjacentes, e ambas correm paralelas (NYLAND et al, 1993).…”
Section: Artérias E Veias Renaisunclassified
“…It can be used in monitoring changes in the perfusion resistance of the renal parenchyma (Silva et al 2008) and high values were found in acute tubular necrosis, renal ischemia, endotoxemia, tubulointerstitial disease and urethral obstruction (Lee et al 2014). Normal values have already been determined for human species (Morrow et al 1996), dogs (Nyland et al 1993) and cats (Finn-Bodner & Hudson 1998).…”
Section: Introductionmentioning
confidence: 99%